A study of thermal conductivity in graphene diodes and transistors with intrinsic defects and subjected to metal impurities. (December 2016) - Sadeghzadeh, Sadegh; Rezapour, Navid
Abstract: In this paper, the effect of the presence of cavities resulting from the fabrication process and the effect of common metal impurities added during the synthesis process on the thermal conductivity of single-layer graphene sheets, diodes and transistors have been investigated by using the Reverse Non Equilibrium Molecular Dynamics (RNEMD) method. The obtained results show that thermal conductivity generally diminishes by increasing the concentration of nanoparticles and increases when porosities and impurities are at the edges of sheets. Regarding a better thermal management in graphene with the addition of nanoparticles, and considering its existing porosity, a lower thermal conductivity is achieved by adding more nanoparticles. By increasing the diameter of pores from 0.5 nm to 4.4 nm in a specific single-layer graphene sheet, thermal conductivity diminishes from 67 W/mk to 1.43 W/mk; while it diminishes from 45 to 1.0 W/mk for the same structure containing both the defects and nanoparticles over the defects. In evaluating the influences of cavities and metallic nanoparticles on thermal conductivity, it was observed that changing the share of cavities or nanoparticles has a significant effect on the thermal conductivity of graphene diodes and transistors. The rectification efficiency of diodes diminished from about 100% for the defect-free diode to about 19% for the diode containing 2 nm cavities and then increased to 75% for the diode with 5 nm cavities. While, with the increase in the concentration of iron nanoparticles, the rectification efficiency increased from about 100% for the diode with no iron particles to about 255% for the diode containing 13 wt % of iron particles. Final results demonstrate that the metallic nanoparticles and also defects with specific diameters can be effectively exploited to increase or decrease the efficiency of nanodiodes and nanotransistors. This leads to engineered design of nanodiodes and nanotransistors for various applications. Highlights: The effect of the cavities and impurities on the thermal conductivity of graphene diodes and transistors is investigated. Thermal conductivity generally diminishes by increasing the concentration of nanoparticles. Thermal conductivity increases when porosities and impurities are at the edges of sheets. Changing the share of cavities or nanoparticles has a significant effect on the thermal conductivity. Nanoparticles and defects can be effectively exploited to change the efficiency of nanodiodes and nanotransistors.